Seamless video handoff in session mobility over the IMS network - Rawashdeh, Majdi (University of Ottawa (Canada), 2009)
Enabling service continuity from one user's device to another while maintaining communications a justifiable ambition; the benefits reaped are maximized end-user service experience and the opportunity to employ the capacities of all devices in the user's environment. Such ubiquity of service can be realized by session mobility between devices. Providing seamless handoff in session mobility is a challenging, and vital, issue relating to the heterogeneous next generation All-IP networks. The research work outlined by this thesis describes a solution to support seamless video handoff in session mobility over IP Multimedia Subsystem (IMS) networks. Our system is built on top of an IMS network, which we believe to be the best platform for session mobility deployment, as it merges mobility and Internet services. The system combines two techniques to achieve seamless video handoff: It uses the SIP REFER method, with a proposed Prediction Handoff Manager that predicts the required handoff time to transfer the session completely. The proposed system is implemented using PJSIP framework, an open source of SIP. Results show effective seamless handover in session mobility over IMS networks.
Keywords: Computer Science.